Numerical Simulation of Mutually Embedded Settlement in Miscellaneous Fill - Fuhai Zhang; Zhengrong Liu; Yu Chen; Liang Chen; Xianwen Huang; Yanhui Bai; Chong Shi; Tianbao Zhou (Advances in Civil Engineering)
Embedding soft soil particles with high moisture content into miscellaneous fill with large pores under overlying loads is easy. It produces mutually embedded settlement, which is an important component of total foundation settlement during calculation. In this study, influences of interface friction on mutually embedded settlement, particle displacement, pore and contact characteristics, and mutually embedded development laws were analysed by using the particle flow method. Research results demonstrate that mutually embedded settlement decreases first and then stabilizes with the increase in contact friction factor and continuously attenuates with normal stiffness. Under the loads, particles at the contact surface move downward and squeeze surrounding particles laterally, thus causing particles to slide at the miscellaneous fill channel upward. Consequently, porosity of particles in miscellaneous fill channel increases. The force chain at the contact surface inclines around, while that at the miscellaneous fill channel presents approximately horizontal distribution. Compared with 35 and 45 mm particles, the mutually embedded settlement of 15 and 25 mm particles is slightly increased with loads. Particle size can relieve the influences of loads on mutual embedding. When particle size is larger than 25 mm, loads can significantly influence mutual embedding. Research conclusions can provide a reasonable theoretical foundation for calculating or predicting settlement of miscellaneous fill-soft soil composite foundation.